Effect of Euphorbia Coagulum on Flexural Property of Polyester Banana Fiber Composite - Rai, Bhuvneshwar; Kumar, Gulshan; Diwan, Rajinder K. (Journal of Research Updates in Polymer Science, 2013)
Presently composites are being made using either both the binder and the reinforcing fibers are synthetic or either one of the material is natural or synthetic. In the present study coagulum (dried latex) of Euphorbia royleana has been used for replacing polyester resin as a natural binder in polyester banana fiber composite. The influence of addition of different weight fraction of the coagulum n flexural property in the composite is studied. It was observed that with the increase in the coagulum fraction in matrix, the flexural property of the polyester banana fiber composite increases. The flexural strength increased by 25% and flexural modulus by 15% at 40% of coagulum weight fraction. This study presents the possibility of preparation of composites using coagulum of Euphorbia latex. The developed composite may be used in partition walls, roof tiles, interior linings of automobiles, etc as wood substitute.